Dynamics of Rabies Epidemics in Vampire Bats. (13th April 2020) - Tian, Liang; Zhang, Juping
Abstract : In order to study the transmission of rabies epidemics in vampire bats, we propose a mathematical model for vampire bat rabies virus. A threshold R 0 is identified which determines the outcome of the disease. If R 0 < 1, the disease-free equilibrium is globally asymptotically stable, and if R 0 > 1, the endemic equilibrium is globally asymptotically stable with certain conditions. Through the numerical simulation, the correctness of the theoretical results is verified. We carry out the sensitivity analysis of the parameters which provide a theoretical basis for preventing and controlling the transmission of bat rabies.